Blood-based systems biology biomarkers for next-generation clinical trials in Alzheimer's disease . Issue 2 (30th June 2019) - Hampel, Harald; Vergallo, Andrea; Afshar, Mohammad; Akman-Anderson, Leyla; Arenas, Joaquín; Benda, Norbert; Batrla, Richard; Broich, Karl; Caraci, Filippo; Cuello, A. Claudio; Emanuele, Enzo; Haberkamp, Marion; et al.
Abstract : Alzheimer's disease (AD)—a complex disease showing multiple pathomechanistic alterations—is triggered by nonlinear dynamic interactions of genetic/epigenetic and environmental risk factors, which, ultimately, converge into a biologically heterogeneous disease. To tackle the burden of AD during early preclinical stages, accessible blood-based biomarkers are currently being developed. Specifically, next-generation clinical trials are expected to integrate positive and negative predictive blood-based biomarkers into study designs to evaluate, at the individual level, target druggability and potential drug resistance mechanisms. In this scenario, systems biology holds promise to accelerate validation and qualification for clinical trial contexts of use—including proof-of-mechanism, patient selection, assessment of treatment efficacy and safety rates, and prognostic evaluation. Albeit in their infancy, systems biology-based approaches are poised to identify relevant AD "signatures" through multifactorial and interindividual variability, allowing us to decipher disease pathophysiology and etiology. Hopefully, innovative biomarker-drug codevelopment strategies will be the road ahead towards effective disease-modifying drugs.